Internet censorship detected in Azerbaijan (Azerbaijan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Azerbaijan. Data sourced from CensoredPlanet.
Censorship Incident ID: AZ-2026-0340. Severity: critical. Confidence: 65%